Revisiting the India’s Southeast Asia policy: An Outlook of the Comparative Study about India’s NDA-UPA Governments - Joyprokash Mondal; Das, Swaraj (Santoso Academy Network, 2023)
From the end of Cold War India has been accelerated to review her foreign policy and also learned specially to revive neighbourhood thinking around her territories. We know, India’s Look East Policy has been accessed now as Act East Policy towards Southeast Asia to East Asia. Now here arises a question why did India need to join with Southeast Asian Association? To explain this paper, we have three objectives like: a) to investigate the roles of different government of India about foreign policy; b) try to search the different approaches from different government if any; c) to draw a layout of India’s Southeast Asian policy. So the research paper will be further search the sufficient role and strategy of United Progressive Alliance (UPA) and National Democratic Alliance (NDA) government from then to till now